Pelatihan Digitalisasi Modul Ajar Kurikulum Merdeka bagi Guru SMP Negeri 2 Tulung - Adi Satrio Ardiansyah; Nuriana Rachmani Dewi; Iwan Junaedi; Devi Ajeng Efrilianda; Mulyono Mulyono; Clara Rosita Hani Yuli Astuti; Dea Erlita; Elsa Fadila Hasaroh (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Technological developments and changes in the curriculum are challenges for teachers to overcome. Presenting digitalized learning and digitalized learning tools is a necessity that needs to be prepared well. A training program that focuses on strengthening teacher literacy and competency in developing digitalized Modul Ajar in Kurikulum Merdeka is the aim of this community service activity. Modul Ajar in Kurikulum Merdeka itself is one of the key learning tools in the learning process, so it needs to be developed well. Systematically, teachers have been given training ranging from socialization activities, demonstrations, mentoring, to evaluation design so that teacher literacy and competence develops. With this activity, not only does teacher literacy and competence develop, but the learning process becomes better quality so that students' learning outcomes can increase.